Empirical Analysis of Flow Characteristics in Physical Activity: Evidence from College Students in Shanghai - Wu, Maoguo; Tan, Min (European Scientific Journal, ESJ, 2018)
Chinese college students’ physical activity mainly consists of physical activity in physical education (PE) classes and extra-curriculum physical activity. With the improvement of college PE teaching, as well as the decline of college students’ physique and the frequent occurrence of psychological problems in college students, more and more Chinese colleges has started promoting students’ active participation in physical activity. This is performed as a means of improving the physique and the mental health of college students. Flow is a positive psychological experience that quite often takes place in physical activity. Based on the theory of flow, this paper investigates flow characteristics in physical activity of college students in Shanghai. Contributing to existing literature on flow, this paper focuses on empirically exploring the manifestation of flow characteristics, differences in flow characteristics in different types of sports, and differences in flow characteristics in different grades of college students in Shanghai. The data are collected from questionnaire survey. Questionnaire questions are based on the Flow State Scale of Jackson and Marsh (1994). A preliminary test was carried out to assess the effectiveness of questionnaire questions. According to test results, a minor amendment of questionnaire questions was made to ensure that all questionnaire questions can be effectively understood. 500 questionnaires are handed out, and all were successfully retrieved. Factor analysis is utilized to reduce dimension, i.e., factorizing the answers to 36 questions into 6 variables and in calculating the value of flow. Test results found that the manifestation of flow characteristics in physical activity of college students in Shanghai are “self-experience”, “integration of action and awareness”, “clear goals and feedback”, “lack of self-consciousness”, “sense of control”, and “time transformation”. There are sharp differences between flow characteristics in physical activity of different types of sports. The flow in closed motor skills physical activity is higher than that in open motor skills physical activity. The main differences are manifested through four factors: self-experience, integration of action and awareness, clear goals and feedback, and sense of control. There are also significant differences among flow characteristics of college students in different grades, with freshmen having the highest value of flow. The flow characteristics of students in different grades also differ in terms of different types of sports.